Profile of seekers of an internet-based self-help program for depression in India: observations and implications - Mehrotra, Seema; Sudhir, Paulomi M.; C. R., Satish Kumar; Thirthalli, Jagadisha; Rao, Girish N.; Srikanth, T. K.; Gandotra, Aditi (International Journal Of Community Medicine And Public Health, 2017)
Background: Growing awareness of treatment gap for common mental health problems has provided an impetus to development of a variety of mental health apps. However there is a dearth of literature on potential users of such apps in India. Information of this nature can be vital in efforts at further development and dissemination of such apps for enhancing their public health impact. Methods: The paper focuses on examining the profile of individuals who expressed an interest in a newly developed internet based self-help program, called PUSH-D (Practice and Use Self-Help for depression). The PUSH-D pilot-trial was announced on various platforms and participation was solicited from individuals in the community. All those who communicated an interest were requested to participate in an initial evaluation session. Hundred and two individuals completed the evaluation that involved use of interviews and standardized questionnaires to assess depression severity, well-being, and functional impairment. Results: An average PUSH-D seeker was likely to be a young adult, with at least undergraduate level of education and was equally likely to be a male or a female. PUSH-D seekers were likely to have major depression or dysthymia; with mild to moderate severity of symptoms and significant impairment in functioning. Co-morbidities were evident only in a minority of PUSH-D seekers. Conclusions: About two third of PUSH-D seekers had never sought mental health services. Various barriers to seeking face to face professional consultations were reported. The results highlight the potential role of internet- based self-help programs for addressing treatment gap in India.